A critical study of the secularism: an alternative to freedom of religion / Abi Mursyidin Awal - Awal, Abi Mursyidin (2008)
This research is simply in regards to the topic of secularism in which whether it can offer solution to the issue of freedom of religion in Malaysia. The reason for us to embark upon such research is due to the fact that suitable remedy is needed to solve the problems faced by the Malaysian court in the recent issue regarding the dual system of civil law and Islamic law operating side by side in Malaysia, particularly on matters relating to freedom of religion. Apart from that, our research will examine the secular system practiced in the United States of America and the republic of Turkey. Within this area, we will touch the historical accounts of how the idea of secularism came into existence and the secular system that is practiced in both countries. In addition, this research also focusing on the freedom, of religion in Malaysia which is guaranteed by the Federal constitution. Moreover, we also intended to discover the conflicting issue arisen in Malaysian legal system and the views of Malaysian regarding secularism on whether it suitable to be implemented in Malaysia. As for the conclusion, our recommendation would be that we acknowledge the inadequacy of the dual legal system practiced in Malaysia. But to opt towards secularism, would actually not offer the solution towards the protection of freedom of religion in this country.